Organization of hospital services for an outbreak of arboviral infections. Cienfuegos 2018 - Carlos García Gómez; María Ocavina Rodríguez Roque; Viviana García Escudero; Andrés Pável Peña Batista; Mailé Ramírez Martínez; Onel Rodríguez Chávez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: arbovirus infections are among the main diseases that affect tropical regions. Within this group, dengue plays a preponderant role. Objective: to describe the organization of medical services in the Dr. Gustavo Aldereguía Lima Hospital in the province of Cienfuegos during the outbreak of cases suspected of arbovirus infections. Methods: descriptive research in the field of the hospital organization of health services in epidemic situations. It was developed between the months of May to December 2018 in the hospital of Cienfuegos. Results: an operative group was created to lead the actions related to the epidemic outbreak for which human resources were trained. The emergency clinical service flow was reorganized to readjust them to the new situation; the elective surgical activity of the hospital was stopped. 150 beds were available for caring of patients with suspected arbovirus infection. All suspicious pregnant women were admitted. No patients were reported dead due to this cause. Conclusions: the organization of the hospital activity in the arbovirus infection outbreak was effective.